Administration of government budgets and the private sector in Nigerian agriculture - Famoriyo, S.; Ingawa, S.A. (1987)
Examines the position of agriculture in federal and state governments' budgets, and reviews the role of the private sector in Nigeria agriculture, w. ref. to the need to revamp the economy, w. recommendations on the integration of the local governments into the process of planning and implementation of all agricultural projects and programmes.